MR Imaging of Pregnant Women with Abdominal Pain and Suspected Appendicitis: Diagnostic Accuracy and Outcomes - Indu Rekha Meesa; Leena Mammen (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Acute appendicitis is the common cause of acute surgical abdomen during pregnancy.Our study was  conducted to review our experience diagnostic accuracy with MRI during pregnancy and  clinical  outcomes over a two year period. All pregnant women who underwent an MRI examination of the  abdomen between January 2008 and January 2010 at Spectrum Health hospitals were included in the  study.We retrospectively reviewed the medical records and MRI findings in 46 pregnant women. 46 pregnant women underwent a total of 53 MRI scans and of these,23/46 (50%) presented with RLQ pain and other signs suspicious for appendicitis. 10/23 (43%) had MRI findings positive for acute appendicitis: 5/10 (50%) had uncomplicated acute appendicitis by MRI criteria, all were confirmed at surgery. 3/5 had a ruptured appendix with abscess,1/5 had a perforated appendix with abscess and 1/5 had MRI findings suspicious for appendicitis but was discharged without surgery or further follow up. The sensitivity for diagnosing appendicitis by MRI in our 10 patients with positive findings was 89% (8 of 9 cases, with one case lost to follow up).The specificity was 100%, since all of the patients who had a normal appendix and/or no secondary signs of appendicitis on MRI were managed medically  and  were  discharged  without  readmission for surgery. The negative predictive value (NPV) was 93% (13/14). Our study shows that MRI of the abdomen without contrast is an excellent alternative to CT and ultrasound for diagnosing and excluding acute appendicitis during pregnancy.